Creativity of Likurai Dance Coreography at Green Dance Studio, Kupang City - Metan, Yosefina; Hartono, Hartono; Wadiyo, Wadiyo (Catharsis, 2019)
Likurai dance is a traditional dance, a type of war dance that is typical of the Belu area, East Nusa Tenggara. The dance is a dance to greet the heroes who come home from the battlefield. Likurai dances are usually performed by several male dancers using swords and female dancers using Tihar or small drums as their dance attributes and are often showed in various events such as welcoming honored guests and traditional ceremonies. Research objective is to analyze the creativity of Likurai dance choreography. The method is interpretative qualitative research method, interdisciplinary approach. Data collection techniques are observations, interviews, and document studies. The validity technique of the data used is source triangulation. The data analysis technique uses the choreography concept according to Hadi Sumandiyo and Muhammad Jazuli. The results of research on creativity in choreography found new ideas in the form of motion, exploration, improvisation, composition. The implications of this research are as an educational media and the local subject of art learning.